FORMULATION AND RELEASE CHARACTERISTICS OF NOVEL MONOLITHIC HYDROXYL PROPYL METHYL CELLULOSE MATRIX TABLETS CONTAINING METRONIDAZOLE - DEEPAK KUMAR MOURYA,; RISHABHA MALVIYA,; MAYANK BANSAL,; PRAMOD KUMAR SHARMA, (International Journal of Pharma and Bio Sciences, 2010)
Monolithic matrix tablets of metronidazole were prepared using hydroxyl propyl methylcellulose (HPMC), Starch 1500 (Prejel®), sodium lauryl sulphate (SLS), microcrystalline cellulose (Avicel® PH101) and sodium dihydrogen phosphate (NaH2PO4) as excipients. Sustained release matrix tablets containing 500 mg metronidazole were developed using different drug polymer ratios of hydroxyl propyl methylcellulose. The m-HPMC tablets were prepared using a wet granulation method followed by direct compression. Sustained release matrix tablets were found to be highly influenced by amounts of m-HPMC polymer incorporated. Results show that granules can be used to prepare tablets in terms of micromeritic properties and flow behavior. Findings of the results show that BatchF1 have maximum drug release while F6 have minimum drug release. It can be concluded from the obtained results that as the concentration of HPMC increases, %drug release decreases.